The Cost-Effectiveness of Developmental Screenings: Evidence from a Nationwide Programme - Martin Halla; Gerald J. Pruckner; Thomas Schober (Institute for the Study of Labor (IZA), 2015)
Early intervention is considered the optimal response to developmental disorders in children. We evaluate a nationwide developmental screening programme for preschoolers in Austria and the resulting interventions. Identification of treatment effects is determined by a birthday cutoff-based discontinuity in the eligibility for a financial incentive to participate in the screening. Assigned preschoolers are about 14 percentage points more likely to participate in the programme. For participants with high socio-economic status (SES), we find little evidence for interventions and consistently no effect on healthcare costs in the long run. For participants with low SES preschoolers, we find evidence for substantial interventions, but only weak evidence for cost savings in the long run.
Keywords: I12; J13; I18; H51; H75; 330; early intervention; child development; developmental disorder; developmental screening; healthcare costs